Pengaruh Bauran Pemasaran Jasa Terhadap Inpatient Satisfaction Rumah Sakit XYZ, Bekasi [The Effect of Service Marketing Mix on Inpatient Satisfaction at Hospital XYZ, Bekasi] - Ginting, Rowny Bernhard (Milestone: Journal of Strategic Management, 2021)
This research was directed to decide the impact of the seven parts of the marketing mix on inpatient satisfaction. This research was conducted at XYZ Hospital Bekasi, involving 100 inpatients. Information assortment was done by appropriating questionnaires containing 40 questions related to marketing mix and satisfaction with a Likert Scale of 1-5 based on convenience sampling method. Data were analyzed by SEM method based on PLS. The aftereffects of this examination found that the seven P marketing mix components (product, price, promotion, place, people, physical evidence, and process) was proven to have a positive impact on patient fulfillment.